Employing consumer knowledge to protect consumer rights - Eshrak Mohsin Al-Jaafari; P. Dr. Nadhum Jawad Abid (Eximia, 2024)
The research aims to measure the level of connection and impact of consumer knowledge in protecting consumer rights, and the sample consisted of (275) consumers in five markets (large retail markets in Baghdad) as they represent the research community of consumers who go to the markets to buy products. The data and hypotheses were analyzed and tested using appropriate statistical tools, including the arithmetic mean and standard deviation to measure the level of descriptive responses of the research sample, correlation coefficients (Pearson) to test the relationships between the research variables, and the simple and multiple linear regression equation to test the effect. The results showed the validity of the research hypotheses, and concluded with a number of Conclusions and recommendations.